SIRT1 Is the Target Gene for 2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-Glucoside Alleviating the HUVEC Senescence - Guo, Yan; Fan, Wenxue; Xie, Yuefeng; Cao, Shuyu; Wan, Haitong; Jin, Bo (Frontiers in Pharmacology, 2020)
This study aimed to explore the effects of 2,3,5,4’-tetrahydroxy-stilbene-2-O-β-d-glucoside (TSG) on the senescence of human umbilical vein cells (HUVEC) induced by hydrogen peroxide (H2O2) and to identify the potential targets mediating its protective action. HUVEC cells pre-treated with TSG for 24 h were exposed to H2O2 treatment. TSG significantly decreased H2O2-induced cellular senescence, as indicated by reduced senescence-associated β-galactosidase (SA-β-gal) positive staining, the proportion of cells in the G1 phase, cell apoptosis, p21, and plasminogen activator inhibitor-1 (PAI-1) expression. Moreover, TSG promoted Sirtuin 1 (SIRT1) expression. When SIRT1 was inhibited by EX527 or SIRT1 siRNA, the effect of TSG is diminished according to the increased proportion of cells in the G1 phase, cell apoptosis, p21, and PAI-1 expression. Overall, our study established TSG as an anti-senescence compound that exerts its protective action by regulating SIRT1 expression.